12 Effect of long-term leucine supplementation on muscle protein synthesis in a pig model of neonatal growth. - Manjarin, R (J Anim Sci, 2018)
Suboptimal nutrient intake represents a limiting factor for growth and long-term survival of low-birth weight infants. Both nutrient intolerance and the risk of developing feeding-related pathologies have led to the implementation of feeding protocols below nutrient requirements, that often result in periods of malnourishment with potential long-term adverse consequences for the neonate. A parallel situation when early growth is compromised is encountered during early weaning of pigs, caused by a reduction in food intake due to stress, environmental changes, and a shift from liquid to solid diet, in conjunction with an increase in nutrient requirements. The resulting growth retardation and mortality represents a major production loss for the swine industry. In the neonate, the primary driving force for the elevated rate of protein accretion is the capacity to attain high rates of protein synthesis after feeding. Studies in neonatal pigs have shown that the sharp increase in muscle protein synthesis after eating is mediated by the rise in amino acids and insulin, which activate independent signaling pathways that converge at mammalian target of rapamycin complex 1 (mTORC1), leading to the activation of key regulators of translation. Leucine is the most effective single amino acid in triggering translation initiation factor activation. Pulsatile administration of leucine during continuous orogastric feeding of a milk replacer during 21 days enhances muscle protein synthesis by stimulating phosphorylation of mTORC1 and its downstream effectors, including ribosomal protein S6 kinase 1 (S6K1) and eukaryotic initiation factor 4 binding protein 1 (4EBP1), while downregulates both cellular autophagy systems and insulin-independent pathways involved in protein catabolism. Prolonged leucine supplementation under protein and energy restriction increases the activation of S6K1 and 4EBP1 but does not improved protein synthesis and body growth in neonates. Whether the anabolic effects of leucine can be sustained chronically to promote lean growth requires further study.